Absence of peripheral blood T cell responses to `shared epitope' containing peptides in recent onset rheumatoid arthritis - McColl, G. (1997)
OBJECTIVES—To determine if peptides containing the `shared epitope' sequence, QKRAA, from either endogenous, HLA-DRβ1(0401), or exogenous, Escherichia coli dnaJ, sources activate T cells in recent onset rheumatoid arthritis (RA). METHODS—Peripheral blood mononuclear cell (PBMC) proliferative and whole blood cytokine responses to shared epitope containing peptides from DRβ1(0401) and E coli dnaJ, to control peptides from DRβ1(0402) and hsp40 and to the recall antigen, tetanus toxoid, were tested in 20 untreated, recent onset RA subjects, 20 HLA, age, and sex matched healthy controls and 18 other subjects with inflammatory arthritis. PBMC proliferative responses to a second E coli dnaJ peptide (with the shared epitope at the N-terminus) and two peptides from type II collagen with high affinity for DR4(0401) were tested in a further 16 recent onset RA and 17 control subjects. RESULTS—PBMC proliferation and whole blood interferon γ or interleukin 10 production in response to the shared epitope containing and control peptides were not different between the disease and control groups. On the other hand, compared with controls, RA subjects had significantly higher proliferation to a collagen II (aa 1307-1319) peptide, but significantly lower proliferation and interferon γ production to tetanus toxoid. CONCLUSION—Recent onset RA subjects had no demonstrable increase in peripheral blood T cell reactivity to shared epitope containing peptides. However, a proportion had increased T cell reactivity to a peptide of similar length from a candidate RA autoantigen, collagen type II. Their impaired responses to tetanus are in keeping with evidence for general T cell hyporesponsiveness in RA.